Uma análise de cluster via CiteSpace a propósito da espectrometria WDXRF para geocientistas (2001-2021) - CASTANHO, Rebeca Soares (Universidade Federal do Pará, 2024)
The present bibliometric analysis addresses the use of Wavelength Dispersive X-Ray Fluorescence (WDXRF) spectrometry in geochemical analysis to evaluate scientific trends over a twenty-year period, from 2001 to 2021, using the academic and free bibliometric tool, CiteSpace. For this purpose, 941 international scientific articles involving WDXRF were collected from the Web of Science (WoS) platform using the search terms "wdxrf" or "wavelength dispersive x-ray fluorescence". The data analysis was divided into two parts: the first part aimed to understand and interpret the quantitative aspects of the scientific production related to the technique, while the second part involved a co-occurrence analysis of keywords from the retrieved works. Despite fluctuations, there has been a constant increase in the number of articles related to this spectrometry technique, with 2020 being the year with the highest productivity in the historical series (105 publications). The United States of America leads the country rankings (110 articles); however, the relatively homogeneous distribution of these studies reveals that WDXRF is a widely disseminated technique worldwide. Brazil ranks among the top ten most influential countries in this field, occupying the eighth position with 59 publications. The journal X-Ray Spectrometry, with 82 articles, stands out as the primary venue for the dissemination of research on this analytical technique. In total, 569 keywords were found, connected by 2002 co-occurrence links. The term "trace element" denotes a solidified but always relevant interest in the use of WDXRF for this level of chemical analysis. On the other hand, "nanoparticle" is the keyword with the highest citation explosion over the past two decades, particularly between 2015 and 2021, highlighting a more recent trend in the elemental characterization of nanostructured compounds. The CiteSpace program identified 13 thematic groups, with five being the most notable in the application of this instrumentation: nanomaterial characterization (cluster #0), trace-level heavy metal analysis (cluster #1), chemical speciation (cluster #2), analysis of particulate matter on filters (cluster #5), and provenance of historical ceramics (cluster #6). In summary, it can be concluded that the chemistry of geological materials does not constitute a narrowly defined body of studies concerning WDXRF. Instead, it represents a scientific frontier that expands through interdisciplinary approaches, providing new and integrated methodological approaches to geoscientific research for those who delve into this technique.